Duran And Kleinert Techniques In Flexor Tendon Rehab: A Comparative Analysis - Rathore, Rohit; Pandey, Manisha; Kumari Singh, Sikha; Pachauri, Drishti; Chandra Bepari, Bidhan; Chadha, Divya; Kashyap, Kriti; Mahek, Mahek; Yusuf, Fatima; Mudgal, Mukul (Journal of Neonatal Surgery, 2025)
Background/Objective- Flexor tendons injuries are one of the most common serious injuries to flexor tendon (flexor digitorum profundus and flexor digitorum superficialis) which are result of lacerations or trauma. The only option of treatment is end to end surgical repair, after which rehabilitation plays a very important role to prevent its recurrence. The aim of this study is to review the rehabilitation techniques i.e. modified Kleinert and modified Duran protocol for flexor tendon injuries. Material and method- A systematic review is done to summarize the benefit of the combined techniques i.e. modified Kleinert and modified Duran protocol. Out of the 28 articles, 10 articles fulfilled our requirement and were put in the inclusion criteria. 18 articles were put in the exclusion criteria as they did not meet our requirement. All the 10 included articles said that modified Kleinert and modified Duran protocol when used in a combination is more successful than when used individually. Result- The result of the review states that the benefit of using the combined protocol is significantly greater than the benefit of using the individual techniques. Discussion- This review incorporates studies that recommend both protocols and propose a change in the technique to allow for movement while avoiding complications of extension. Functional outcomes tend to be better when a balanced rehabilitation protocol is followed as suggested by the review findings. Conclusion- This review found out that modified kleinert and modified duran protocol when used in a combination is more successful and productive.